Wait's complex-image principle generalized to arbitrary sources. - Lindell, I.V (IEEE Transactions on antennas and propagation)
The well-known simple and remarkably accurate approximate low-frequency (LF) complex-image method introduced in 1969 by J. R. Wait to compute the effect of the ground to the field of a divergenceless horizontal current (vertical magnetic current) is generalized to arbitrary current sources through the exact image formulation. The images of a vertical dipole, a horizontal current segment, and an oscillating point charge are first reduced to simplified but asymptotically exact forms and, subsequently, in terms of delta and step-functions to approximate image expressions that also include Wait's image. The novel part of the image is tested numerically through a geophysical example